DO EFL STUDENTS LIKE GRADED READERS? - Kenneth M. Smith; Stephen Krashen (Universitas Katolik Indonesia Atma Jaya, 2009)
Graded readers are widely used in English as a foreign language programs, but we have little information about whether students find them interesting. In this study, 14 to 16 year old students of English as a foreign language in Taiwan were asked to evaluate the readers they had read. Overall, 41% found the books to be interesting, and 24% did not, but only 4% strongly agreed that the books were interesting. This is an encouraging result, but if our goal is to help students find truly compelling reading material, we will have to look elsewhere for additional reading material.Keywords: Graded readers, English as a foreign language, reading material.